A Systematic Review of the Diagnostic Value of CT Imaging in Diagnosing Otosclerosis. Issue 1 (January 2016) - Wegner, Inge; van Waes, Anne M. A.; Bittermann, Arnold J.; Buitinck, Sophie H.; Dekker, Caroline F.; Kurk, Sophie A.; Rados, Matea; Grolman, Wilko
Abstract : Objective: To evaluate the diagnostic value of computed tomography (CT) in detecting otosclerosis in patients with conductive hearing loss and a clinical suspicion of otosclerosis. Data Sources: PubMed, Embase, and the Cochrane Library. Study Selection: A systematic search was conducted. Studies reporting original study data were included. Data Extraction: Relevance and risk of bias of the selected articles were assessed. Studies with low relevance, high risk of bias, or both were excluded. Prevalences, sensitivities, specificities, and post-test probabilities were extracted from the included articles. Data Synthesis: Seven studies characterized by a moderate to high relevance and moderate to low risk of bias were included for data extraction. The prevalence of otosclerosis was high (up to 100%) in the majority of the included studies. In those studies with a high prevalence of disease, both positive and negative post-test probabilities were (relatively) high: 99% and between 51% and 67% respectively. In one study with a low prevalence of disease (9%), both positive and negative post-test probabilities were low (23% and 3% respectively). Overall, reported sensitivities ranged between 60% and 95%. Conclusion: Preoperative CT has little to add in establishing otosclerosis and may not be necessary to confirm the diagnosis. We would recommend reserving CT for those patients with suspected additional abnormalities, for specific preoperative planning, or out of legal necessity.